أثر السياسات المالية على ميزان المدفوعات السوداني 1990-2011م - د. الشاذلي عيسى حمد عبد الله (White Nile Journal for Studies and Research, 2014)
This study investigates the impact of financial policies on the balance of payments. In Sudan during the period 1990-2011, it hypothesized that these policies have a positive impact on balance of payments during the period of the study. After doing the necessary computation using the computer facilities the study found that the increase in budget defect had a negative impact on the balance of payments. This is resulted from the fact that this defect was manipulated by borrowing from the banking system which lead to an increase in money supply which inturn aggravated rates of inflation and reduced the competing ability of exports. Finally, the study recommended that the situation of Sudanese balance of payments could be improved by reduction of production cost achievement of fair peace in Sudan and reducing borrowing from the banking system.